NGOPI BARENG SEBAGAI MEDIA KOLABORASI PEMERINTAH DESA DAN NU: PRAKTIK PENGABDIAN DI KAMPUNG NU BANYUWANGI - Muhammad Sahlan; Ainur Rofiq (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2025)
This article examines the implementation of the Ngopi Bareng (Casual Coffee Gathering) program as a collaborative medium between the Village Government and the local Nahdlatul Ulama (NU) leadership in supporting community development in Kampung NU, Banyuwangi. Designed as an informal dialogue forum, Ngopi Bareng provides an egalitarian space where village officials, NU leaders, and community members engage in open discussion. Within this relaxed setting, participants address various social, cultural, religious, and public service issues that shape everyday life in the village. The community engagement approach used in this program is participatory in nature, involving regular meetings, focused group discussions, and experience-sharing sessions that emphasize deliberation (musyawarah), collective action (gotong royong), and a human-centered orientation. The results of this engagement indicate that Ngopi Bareng successfully increases public participation in village programs, strengthens social networks between the village administration and religious communities, and stimulates the emergence of innovative local initiatives aligned with community needs. Additionally, the activity reinforces local wisdom and NU traditions, particularly in cultivating a culture of dialogue, tolerance (tasamuh), and social responsibility. Program sustainability is maintained through the establishment of routine forums and the expansion of collaborative networks, ensuring that Ngopi Bareng evolves beyond a one-time activity into a sustainable partnership model that can be replicated in other villages. The findings affirm that community-based dialogue platforms grounded in religious and cultural values are highly effective in fostering social harmony, enhancing local capacity, and promoting inclusive and participatory village development innovations.